Recent Progress towards the Transition-Metal-Catalyzed Dearomatizing Spirocyclization Reactions of Indolyl Ynones - Wei, Kua-Fei; Jiang, Xiao-Lei; Ru, Guang-Xin; Zhu, Xiu-Hong; Shen, Wen-Bo (Synlett, 2022)
Dearomatizing spirocyclization reactions are very appealing synthetic strategies to generate functionalized three-dimensional scaffolds from simple two-dimensional precursors. Recently, the field of transition-metal-catalyzed dearomatizing spirocyclization reactions of indolyl ynones has burgeoned, as the construction of synthetically challenging quaternary spirocyclic carbons is easily achieved. In this review, we introduce an overview of advances in the transition-metal-catalyzed dearomatizing spirocyclization reactions of indolyl ynones, with the reactions being categorized according to type of catalyst.
Keywords: transition-metal catalysis; indolyl ynones; dearomatization; spirocyclization; spirocyclic indolenines